State of leisure studies in Australia and New Zealand. Issue 1 (2nd January 2018) - Tower, John; McGrath, Richard; Sibson, Ruth; Adair, Daryl; Bevan, Nadia; Brown, Graham; Foley, Carmel; Fullagar, Simone; Gray, Lyndal; Hawkins, Clayton; Jeanes, Ruth; Kerr, Roslyn; et al.
ABSTRACT: A recurring theme has emerged from past ANZALS (Australia and New Zealand Association for Leisure Studies) Conferences' keynote presentations concerning the status of leisure studies from a teaching and research perspective. While this broad discussion has been raised, little is formally known about the current status of leisure studies in Australian and New Zealand universities. The ANZALS Board initiated a project in 2015 to gain insights into this topic. The purpose of the project was to document issues about leisure studies in Australian and New Zealand universities and to explore strategies that could assist ANZALS to promote leisure studies across various sectors. This initiative sought feedback from the ANZALS Patron organisations as well as members via a workshop conducted at the 2015 ANZALS Conference. Outcomes from the project have identified leisure studies as a diverse and disparate field of study. Leisure studies is no longer a centralised field within Australian and New Zealand universities. Instead, leisure studies have become divergent and focused on the elements within leisure such as recreation, sport, tourism and events, as well as across domains such as management and health. The project outcomes indicate the need for organisations such as ANZALS to develop and maintain collaborative networks with a variety of stakeholders, both within the tertiary sector as well as amongst practitioners in various industry sectors. There is also a need for ANZALS and kindred organisations to recognise and acknowledge the past and ensure its future by examining how leisure studies can be defined for application in a realm of related fields of study.